2016
DOI: 10.1108/mmms-04-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

A computational analysis of the utility of chemical reactions within protective structures in mitigating shockwave-impact effects

Abstract: Purpose The purpose of this paper is to introduce and analyze a new blast-wave impact-mitigation concept using advanced computational methods and tools. The concept involves the use of a protective structure consisting of bimolecular reactants displaying a number of critical characteristics, including: a high level of thermodynamic stability under ambient conditions (to ensure a long shelf-life of the protective structure); the capability to undergo fast/large-yield chemical reactions under blast-impact induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Considering the various loads in the design, the same modeling method was applied to the finite element analysis of the real bridge. After analysis, he finally confirmed that this new type of bridge meets the specifications for strength, stiffness, and crack resistance [8]. Chen believes that the construction of transportation infrastructure has a profound impact on the coordinated development of the regional economy and urban agglomerations.…”
Section: Introductionmentioning
confidence: 84%
“…Considering the various loads in the design, the same modeling method was applied to the finite element analysis of the real bridge. After analysis, he finally confirmed that this new type of bridge meets the specifications for strength, stiffness, and crack resistance [8]. Chen believes that the construction of transportation infrastructure has a profound impact on the coordinated development of the regional economy and urban agglomerations.…”
Section: Introductionmentioning
confidence: 84%
“…The specific chemical reaction investigated by Grujicic, Snipes and Ramaswami (2016) involved polyvinyl pyridine, (-CH 2 -CH(C 5 H 4 N)-) n , and cyclohexyl halides, (C 6 H 7 R 2 R′ 2 X; X ¼ Cl, Br, I; R,R′ are functional groups), as reactants, and ionic pyridinium salt (-CH 2 -CH (C 5 H 4 N + -C 6 H 7 R 2 R′ 2 )-) n •nXas product. Molecular configurations of the reactants and the products of this reaction are depicted in Figure 1.…”
Section: Ijsi 82mentioning
confidence: 99%
“…reactions wherein the transition state has a cyclic geometry and the reaction progresses in a concerted fashion) may occur (Davis et al, 2009). In our prior work (Grujicic, Snipes and Ramaswami, 2016), the following two families of chemical reactions have been identified as potentially possessing the four characteristics described above: ionic-particle-formation reactions (described in greater detail below); and Diels-Alder reactions (organic reactions between a 1, 3-conjugated four-carbon linear chain (like 1, 3-butadiene) and a substituted two-carbon alkene (i.e. ethene) to form a substituted cyclohexene).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations